Pengaruh Sikap terhadap Kepatuhan Perawat pada Penerapan Budaya Keselamatan Pasien di RS Mitra Sejati - Hernawati Hernawati; Zulfendri Zulfendri; Siti Saidah Nasution (Syntax Corporation Indonesia, 2021)
The application of a patient safety culture such as reporting and recording patient safety incidents at Mitra Sejati Hospital has not been implemented well since most of its nurses do not comply with the rules such as they do not report the incidence since they think that it is not serious enough and they are afraid of reporting it to the management. The objective of the research was to analyze in the influence of individual characteristics and leadership style on nurses’ compliance with patient safety at Mitra Sejati Hospital. The research used explanatory method with cross sectional design. The population was 132 patients, and 57 of them were used as the samples. The data were gathered by using questionnaires and by using multiple linear regression tests at the significance level of 95%. The results showed that there were 64.9% of nurses who were less obedient in implementing a patient safety culture, while those who were obedient were 15.8%. Individual characteristic variables include attitude (p = 0.041) and leadership style variables (p = 0.029) have an effect on nurses' compliance with the application of patient safety culture. The dominant variable that has the most influence is leadership style with a coefficient value of β = 0.350, meaning that if the head of the room applies a leadership style it will result in an increase in nurse compliance with the application of patient safety culture by 0.350. The nurse's assessment of the headroom's leadership style that is most preferred is the participatory leadership style. It is recommended that the hospital provide training on patient safety to improve the attitude of nurses in realizing potential events or injuries that are more dangerous to patients, so that each head of the room can be a role model for implementing nurses to comply with a patient safety incident reporting culture.